2021
DOI: 10.1161/circgen.120.003106
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Score for Low-Density Lipoprotein Cholesterol Is Associated With Risk of Ischemic Heart Disease and Enriches for Individuals With Familial Hypercholesterolemia

Abstract: Background - The clinical implications of a polygenic risk score (PRS) for low-density lipoprotein cholesterol (LDL-C) are not well understood, both within the general population and individuals with familial hypercholesterolemia (FH). Methods - We developed the LDL-C PRS using LASSO regression in 377,286 white British participants from UK Biobank and tested its association with LDL-C according to FH variant carrier status in another 41,748 whole-exome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
0
17
2
3
Order By: Relevance
“…High serum LDL-C levels are one of the leading causal factors for CAD, and thus PRS LDLC , which increased LDL-C, could also be associated with CAD in European ancestry. [9,35,37,38] For the FH groups in this study, since PRS LDLC was not linked to the LDL-C levels, it may be that there was no relationship between PRS LDLC and CAD. However, for the control group, we could not detect any association between PRS LDLC and CAD, despite the apparent correlation between PRS LDLC and LDL-C levels.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…High serum LDL-C levels are one of the leading causal factors for CAD, and thus PRS LDLC , which increased LDL-C, could also be associated with CAD in European ancestry. [9,35,37,38] For the FH groups in this study, since PRS LDLC was not linked to the LDL-C levels, it may be that there was no relationship between PRS LDLC and CAD. However, for the control group, we could not detect any association between PRS LDLC and CAD, despite the apparent correlation between PRS LDLC and LDL-C levels.…”
Section: Discussionmentioning
confidence: 74%
“…Trinder et al demonstrated that a distribution of PRS LDLC for FH patients was right-skewed (higher overall) compared with that of the 1000 Genomes reference population [9]. Also, Wu et al reported that mutation negative CDFH patients had a higher effect size on PRS LDLC unit increase than on monogenic FH [35]. Despite comprehensive genomic analysis by highthroughput sequencing, we still do not know the causative monogenic variants in one fourth of CDFH patients [5].…”
mentioning
confidence: 99%
“…Such changes are captured in a polygenic risk score. So far, multiple polygenic risk scores have been developed for increased LDL-c levels using population data, including scores based on only six SNPs or based on hundreds of SNPs; however, these still need proven validation, clinical validity, and utility in hypercholesterolemia [64][65][66]. Such scores may explain high LDL-c levels in an individual or explain variance in LDL-c levels within FH families, but it is still debatable whether they are clinically actionable.…”
Section: Future Directionsmentioning
confidence: 99%
“…Благодаря регистру Simon Broome сделан вывод, свидетельствующий о том, что наличие СГХС при условии отсутствия лечения увеличивает риск смерти от ССЗ в 100 раз в возрасте 20-39 лет и в 4 раза -в возрасте 40-59 лет [26]. Влияние уровня ЛПНП на частоту ССС у пациентов с СГХС изучено в нескольких работах [27][28][29]. Поскольку данные пациенты имели высокий уровень холестерина ЛПНП с рождения [30], дебют острого коронарного синдрома у них происходил в более молодом возрасте, чем у пациентов без СГХС [1,22].…”
unclassified
“…Результаты показали, что моногенная причина СГХС связана со значительно более высоким риском ССЗ, тогда как риск ССЗ у пациентов с полигенной СГХС и у тех, у которых генетическая причина СГХС не выявлена, не различается. Данное исследование демонстрирует важность генетического тестирования для определения прогноза пациентов с СГХС, что доказано в ряде других работ [29,[49][50][51].…”
unclassified